Influence of water content on elastohydrodynamic friction and film thickness of water-containing polyalkylene glycols - Hofmann, Stefan; Lohner, Thomas; Stahl, Karsten (Frontiers in Mechanical Engineering, 2023)
Lubricants with a functional water portion have demonstrated a drastic reduction in friction under elastohydrodynamic lubrication conditions. With water-containing polyalkylene glycols, superlubricity with coefficients of friction <0.01 have been measured in model and gear contacts. In addition to the low friction, their calorimetric properties make them particularly interesting for application in electrified vehicles because the liquid can simultaneously serve as lubricant for the gearbox and coolant for the electric motors and the power electronics. In this study, the influence of water content between 8 wt% and 40 wt% of water-soluble polyalkylene glycols on friction and film thickness in elastohydrodynamically lubricated rolling-sliding contacts such as in gears and bearings is investigated. A polyalphaolefine oil is used as a reference. Friction has been measured on a ball-on-disk tribometer and film thickness on an optical tribometer. For a water content of 40 wt%, superlubricity with coefficients of friction down to 0.004 are found. The decrease in friction is up to 95% compared to the polyalphaolefine reference. The measured film thickness decreases with increasing water content. For a water content of 8 wt%, the film thickness is similar to that of the polyalphaolefine reference while at the same time friction is still reduced by 81%. Depending on the friction and film thickness requirements of a specific tribosystem, the water content of a water-containing polyalkylene glycol can be chosen accordingly.